Globales Informationssystem Zünslerfalter (GlobIZ). - Nuss, Matthias; Segerer, Andreas H. (Contributions to Entomology = Beiträge zur Entomologie, 2005)
The Global Information System on Pyraloidea (GlobIZ) is a web-based database. It allows the editing of nomenclatural and bibliographical data simultaneously by several users. GlobIZ provides a synonymic catalogue of the names of Pyraloidea (Insecta: Lepidoptera), including the relevant literature references. This information is universally available and free of charge via the world wide web. Originally, the project was restricted to the Pyraloidea, but several systematists of other groups of Lepidoptera, e. g. Psychidae, have signalled their interest to work with this system. GloBIZ is part of the German National GBIF node Insecta (Evertebrata I).